Relationship status and gender-related differences in response to infidelity - Kato, Tsukasa; Okubo, Nobutoshi (Frontiers in Psychology, 2023)
The sexual imagination hypothesis suggests that responses to a partner’s infidelity emerge from the sociocultural factors that affect individuals’ imagining of that occurrence irrespective of biological sex, including relationship status (i.e., the experience of a serious, committed relationship). Nevertheless, evolutionary psychological perspectives predict that responses to a partner’s infidelity emerge from a sex-specific evolved innate mechanism. A lower 2D:4D digit ratio is associated with more robust responses to a partner’s sexual infidelity. In this study, participants (660 males and 912 females) were requested to measure finger lengths, reactions to their partners’ sexual and emotional infidelity, and relationship status. A logistic regression and multiple regression analyses revealed that relationship status was uniquely associated with responses to a partner’s sexual and emotional infidelity beyond the effects of sex and 2D:4D. Those in committed relationships were more upset or distressed over their partners’ infidelity, particularly over sexual infidelity, than those not in committed relationships. The results supported the sexual imagination hypothesis indirectly, while evolutionary psychological perspectives were met with skepticism. Our findings implied that sex differences in jealousy result from relationship status, and that responses to partners’ infidelity are more alike than different.